MODERN WAYS OF LEARNING FOREIGN LANGUAGE BY USING IT FOR NON-PHILOLOGICAL STUDENTS (Proceedings of International Educators Conference, 2023)
Throughout the previous two decades, Uzbekistan's education system has grown significantly, resulting in structural changes and creative new initiatives. Yesterday, the President of Uzbekistan issued a proclamation that was printed and distributed. This strategy requires extensive investigation into a wide range of issues. Then we can finish it. Due to the book's importance, reading non-native literature, especially English ones, has been included into secondary school curriculum nationwide starting in first grade. This applies especially to schools in English-speaking states.